Exploring the Relationship between Country Risk and Foreign Private Investment Inflows in Pakistan. (December 2016) - Ullah, Assad; Qingxiang, Yang; Ali, Zahid; Hidayat, Nadia
Secure investment climate of the host country can augment the inflows of foreign investment and vice versa. This article examines the relationship between country risk and foreign private investment (FPI) in Pakistan. The study utilises the technique of Autoregressive Distributed Lag (ARDL) bounds testing to co-integration over the period 1990–2013. Stationarity property of the series has been checked via Phillips–Perron unit root test. The study confirms presence of co-integration among country risk, trade openness, military expenditure and FPI, thereby giving validation of long-term association among the variables. The study transpires a negative and significant link between country risk and FPI in the long-run whereas, in the short run, the result came out to be inconclusive. Openness in the economy has significant positive relationship with FPI inflows both in the long and short run. Finally, military expenditure has a significant negative effect on FPI inflows in the long run while, in the short run, the result is otherwise. According to modified WALD (MWALD) test, a unidirectional causality is running from country risk, military expenditure and trade openness to FPI in Pakistan. To entice more inflows of FPI, concerned authorities in Pakistan need to control sectarian violence and other terrorist activities. In this regard, the policymakers need to design robust strategic plans and systems beside the traditional security measures.